THE HEDONIC CONFORMITY AND IMPULSIVE TENDENCIES ON THE CONSUMER BEHAVIOR OF THE PEOPLE IN CENTRAL TERNATE CITY MEDIATED BY CONSUMER LIFESTYLE - Sapsuha, Mizwar; Subhan; Panigoro, Safri; Sardju, Himawan; Aris, Iqbal M (Ecopreneur.12, 2024)
This research used a sample of 135 respondents determined using the Random Sampling techniquewhere the sample in this research consisted of respondents who had different characteristics atdifferent levels of society in Central Ternate City. The data analysis method used in this research isSPSS and PLS (Partial Least Square) with analysis test tools using IBM SPSS Statistics 20 andSmartPLS version 3.0. From the results of hypothesis testing and discussion, the followingconclusions can be drawn from this research: Hedonic conformity partially has a positive andsignificant effect on the consumptive behavior of the people of Central Ternate, this shows that theexistence of hedonic conformity that occurs in the people of Central Ternate is positive, and theimplications of hedonic conformity give rise to actions in consuming (consumptive behavior). Thepartial impulsive tendency does not have a positive and significant influence on consumer behavior,meaning that before making a purchase, the people of Central Ternate city have thought aboutplanned actions regarding the goods they will buy. The limitations of this research are that hedonicconformity partially has a positive and significant effect on the consumptive behavior of the peopleof Central Ternate. This shows that the existence of hedonic conformity that occurs in the people ofCentral Ternate is positive, and the implications of hedonic conformity give rise to actions inconsuming (behavior consumptive). The partial impulsive tendency does not have a positive andsignificant influence on consumer behavior, meaning that before making a purchase, the people ofCentral Ternate city have thought about planned actions regarding the goods they will buy. Hedonicconformity partially has a positive and significant effect on the consumer lifestyle of the people ofCentral Ternate, this shows that there is a strong influence from the group on the choice of productsor goods to be purchased.